DETERMINANTS OF TAX AVOIDANCE IN MANUFACTURING COMPANIES - Permatasari, Dyah Ayu Dewi; Muniroh, Hetty (Program Studi Diploma III Akuntansi Fakultas Ekonomi dan Bisnis Universitas Mataram, 2024)
This research examines the effect of inventory intensity, capital intensity, financial distress, and financial lease on tax avoidance in manufacturing companies listed on the IDX for 2019–2021. Documentation techniques were used to collect data in this research, while a purposive sampling approach was used to produce samples that met the research requirements. There were 52 firms in the research sample, totaling 156 observations. In this research, SPSS software was used to test multiple linear regression analysis data techniques previously examined using classical presumptions to obtain the Best Linear Unbiased Estimate (BLUE) data. The results showed that inventory intensity positively and insignificantly influenced tax avoidance. In contrast, capital intensity, financial distress, and financial leases significantly negatively affected tax avoidance.